ナンキョク カイ エンガン イキ ノ クロロフィル a ノ スイチョク テキ ブンプ ト ゲンゾン リョウ - 大野, 正夫; オオノ, マサオ; 福田, 靖; フクダ, ヤスシ; 福地, 光男; フクチ, ミツオ; Ohno, Masao; Fukuda, Yasushi; Fukuchi, Mitsuo (1987)
P(論文) 第26次南極地域観測隊ではBIOMASS SIBEX IIの計画の一環として, 1984年12月から1985年2月にかけて東南極海沿岸域のクロロフィルa量の垂直分布と現存量の調査が行われた。調査はブライド湾(70°05′-70°15′S, 23°50′-24°20′E)で12月と2月の2回, 9定点で行われ, グンネルス・バンク(68°00′-68°23′S, 30°00′-35°00′E)トリュツォ・ホルム湾(67°00′-68°00′S, 36°00′-38°00′E)では2月にそれぞれ7定点で行われた。水温は-1.87℃から2.1℃, 塩分は32.63から34.63の範囲内にあった。ブライド湾では, 12月には上層(0-50m)でクロロフィルa量は高い値を示し, 0-200m水柱内のクロロフィルa積算値は230.0-410.7mg/m^2であった。2月には, その値は95.1-207.2mg/m^2と減少していた。グンネルス・バンクとリュツォ・ホルム湾のクロロフィルa積算値は, それぞれ41.9-116.5mg/m^2と46.0-78.3mg/m^2であり, やはり上層で高い値を示したが, ブライド湾の値と比較して低い値であった。 Japanese BIOMASS SIBEX II program was carried out partly by the 26th Japanese Antarctic Research Expedition from December 1984 to February 1985. The vertical distributions of chlorophyll a, phaeophytin and oceanographic parameters to a depth of 200m were investigated in three areas; 9 stations in Breid Bay (70°05′-70°15′S, 23°50′-24°20′E), 7 stations off the Gunnerus Bank (68°00′-68°23′S, 30°00′-35°00′E) and 7 stations off Lutzow-Holm Bay (67°00′-68°00′S, 36°00′-38°00′E) in the Antarctic coastal waters. Water temperature ranged from -1.87 to 2.1℃, and salinity ranged from 32.63 to 34.63. Salinity was 32.63-33.95 throughout the upper 0-50m layer, in which chlorophyll a was abundant. In Breid Bay, integrated chlorophyll a stocks (0-200m) decreased from 230.0-410.7mg/m^2 in December to 95.1-207.2mg/m^2 in February. In the waters off Lutzow-Holm Bay, the stocks remained between 46.0 and 78.3mg/m^2. The phaeophytin content was large at almost all the stations. departmental bulletin paper